(untitled) (Jóvenes en la Ciencia, 2024)
Tetrahydrocannabinol, or THC, is a chemical compound that has been the subject of increasing interest in the medical field as an alternative therapy for patients facing chronic illnesses. In this article, the objective was to explore the prevalence of THC use and knowledge in the management of chronic diseases. A descriptive study was carried out with a sample of 40 people who were chosen at convenience by applying the Muñoz, E. (2015) questionnaire. It was shown that there is a minimum consumption of THC that corresponds to 10% of the total population to counteract symptoms of different chronic diseases. With respect to knowledge, it was shown that they have a satisfactory level.